Ramanujan's Published Paper
Ramanujan's Published Paper
Ramanujan's Published Paper
theory of numbers
Transactions of the Cambridge Philosophical Society, XXII, No.13, 1918, 259 276
1. The trigonometrical sums with which this paper is concerned are of the type
X 2n
cs (n) = cos ,
s
xs 1 = 0.
These sums are obviously of very great interest, and a few of their properties have been
discussed already . But, so far as I know, they have never been considered from the point
of view which I adopt in this paper; and I believe that all the results which it contains are
new.
My principal object is to obtain expressions for a variety of well-known arithmetical func-
tions of n in the form of a series X
as cs (n).
s
A typical formula is
2n
c1 (n) c2 (n) c3 (n)
(n) = + 2 + 2 + ,
6 12 2 3
where (n) is the sum of the divisors of n. I give two distinct methods for the proof of this
and a large variety of similar formul. The majority of my formul are elementary in
the technical sense of the word they can (that is to say) be proved by a combination
of processes involving only finite algebra and simple general theorems concerning infinite
series. These are however some which are of a deeper character, and can only be proved
by means of theorems which seem to depend essentially on the theory of analytic functions.
A typical formula of this class is
a formula which depends upon, and is indeed substantially equivalent to, the Prime Num-
ber Theorem of Hadamard and de la Vallee Poussin.
Many of my formul are intimately connected with those of my previous paper On certain
arithmetical functions, published in 1916 in these Transactions . They are also connected
(in a manner pointed out in 15) with a joint paper by Mr Hardy and myself, Asymptotic
Formul in Combinatory Analysis, in course of publication in the Proceedings of the
London Mathematical Society .
But from (2.3) we know that (n) = 0 if is not a divisor of n; and so we can suppose
that, in (2.7), is a common divisor of n and s. It follows that
X
|cs (n)| ,
c6 (n) = 1, 1, 2, 1, 1, 2 : c7 (n) = 1, 1, 1, 1, 1, 1, 6;
c8 (n) = 0, 0, 0, 4, 0, 0, 0, 4; c9 (n) = 0, 0, 3, 0, 0, 3, 0, 0, 6;
c10 (n) = 1, 1, 1, 1, 4, 1, 1, 1, 1, 4; . . . . . .
the meaning of the third formula, for example, being that c3 (1) = 1, c3 (2) = 1, c3 (3) = 2,
and that these values are then repeated periodically.
It is plain that we have also
3. Substituting (2.6) in (2.4) and collecting the coefficients of c1 (n), c2 (n), c3 (n) . . . , we
find that
(3.1)
1 1
t 2t 3t
X 1 n X 1 n X 1 n
D(n) = c1 (n) F , + c2 (n) F 2, + c3 (n) F 3, + ,
2 2 3 3
1 1 1
where t is any number not less than n. If we use (2.2) instead of (2.1) we obtain another
expression, viz.
(3.2)
1 1
t 2t 3t
X 1 n X 1 n X 1 n
D(n) = c1 (n) F , + c2 (n) F , 2 , +c3 (n) F , 3 + ,
1
1
2 2 1
3 3
Then we have
X X
D(n) log n = F (, ) log n = F (, ) log( )
X X
= F1 (, ) + F2 (, ),
Now for F1 (, ) we shall write the expression corresponding to (3.1) and for F2 (, )
P P
where r and t are any two numbers not less than n. If, in particular, F (u, v) = F (v, u),
then (3.3) reduces to
t
1
X log n
(3.4) 2 D(n) log n = c1 (n) F ,
1
1 1
2t 3t
X log 2 n X log 3 n
+ c2 (n) F 2, + c3 (n) F 3, + ,
2 2 3 3
1 1
where is a divisor of n, = n, and u, v are may two positive numbers such that uv = n,
it being understood that, if u and v are both integral, a term F (u, v) is to be subtracted
from the right-hand side. Hence (with the same conventions)
u v
X 1 n X 1 n
D(n) = (n)F , + (n)F , ,
1 1
where u and v are positive numbers such that uv = n. If u and v are integers then a term
F (u, v) should be subtracted from the right-hand side.
If we suppose that 0 < u 1 then (4.2) reduces to (3.2), and if 0 < v 1 it reduces to
(3.1). Another particular case of interest is that in which u = v. Then
n
X 1 n n n o
(4.3) D(n) = c1 (n) F , +F ,
1
1
2Xn
1 n n n o
+ c2 (n) F 2, +F , 2 + .
1
2 2 2
If n is a perfect square then F ( n, n) should be subtracted from the right hand side.
5. We shall now consider some special forms of these general equations. Suppose that
F (u, v) = v s , so that D(n) is the sum s (n) of the sth powers of the divisors of n. Then
from (3.1) and (3.2) we have
1 1
t 2 t 3 t
s (n) X 1 X 1 X 1
(5.1) = c1 (n) + c2 (n) + c3 (n) + ,
ns 1
s+1 1
(2)s+1 1
(3)s+1
1 1
t 2 t 3 t
X X X
(5.2) s (n) = c1 (n) s1 + c2 (n) (2)s1 + c3 (n) (3)s1 + ,
1 1 1
where r and t are two numbers not less than n: and from (4.2)
1 1
u 2 u 3 u
X X X
s1
(5.4) s (n) = c1 (n) + c2 (n) (2)s1 + c3 (n) (3)s1 +
1 1 1
1 1
v 2v 3v
X 1 X 1 X 1
+ ns c1 (n) + c2 (n) + c3 (n) + ,
s+1 (2)s+1 (3)s+1
1 1 1
On certain trigonometrical sums and their applications in the theory of numbers 235
where uv = n. If u and v are integers then us should be subtracted from the right-hand
side.
Let d(n) = 0 (n) denote the number of divisors of n and (n) = 1 (n) the sum of the
divisors of n. Then from (5.1) (5.4) we obtain
1 1
t 2 3 t t
X 1 X 1 X 1
(5.5) d(n) = c1 (n) + c2 (n) + c3 (n) + ,
1
1
2 1
3
1 1
t 2 t 3 t
1
X log X log 2 X log 3
(5.7) 2 d(n) log n = c1 (n) + c2 (n) + c3 (n) + ,
1
1
2 1
3
1 1
( u v
) 2 u 2 v
X 1 X 1 X 1 X 1
(5.8) d(n) = c1 (n) + + c2 (n) +
2 2
1 1 1 1
1 1
3u 3v
X 1 X 1
+ c3 (n) + +
1 3
1
3
where t n and uv = n. If u and v are integers then 1 should be subtracted from the
right-hand side of (5.8). Putting u = v = n in (5.8) we obtain
1 1
n 2X 3X n n
1
X 1 1 1
(5.9) 2 d(n) = c1 (n) + c2 (n) + c3 (n) + ,
1
1
2 1
3
unless n is a perfect square, when 12 should be subtracted from the right-hand side. It may
be interesting to note that, if we replace the left-hand side in (5.9) by
1 1
2 + 2 d(n) ,
6. So far our work has been based on elementary formal transformations, and no questions
of convergence have arisen. We shall now consider the equation (5.1) more carefully. Let
us suppose that s > 0. Then
t/k
X 1 X 1 1 1 1
s+1
= +O = (s + 1) + O .
(k) (k)s+1 kts ks+1 kts
1 1
236 Paper 21
The number of terms in the right-hand side of (5.1) is [t]. Also we know that c (n) = O(1)
as n . Hence
t t
( )
s (n) X c (n) 1 X1 X c (n) log t
= (s + 1) +O s = (s + 1) +O .
ns s+1 t s+1 ts
=1 =1 1
Making t , we obtain
s c1 (n) c2 (n) c3 (n)
(6.1) s (n) = n (s + 1) + s+1 + s+1 + ,
1s+1 2 3
But
X log k log k 1
s+1
= s+1 (s + 1) s+1 (s + 1).
(k) k k
1
2
c1 (n) c2 (n) c3 (n)
(6.3) (n) = n + 2 + 2 + ,
6 12 2 3
(2) 2
c1 (n) c2 (n)
(6.4) (n) + log n = n 2
log 1 + 2 log 2 +
(2) 6 1 2
+ c1 (n)[t] log 1 + c2 (n)[ 12 t] log 2 +
+ c1 (n) log[t]! + c2 (n) log[ 21 t]! + ,
On certain trigonometrical sums and their applications in the theory of numbers 237
where t n.
7. Since
where s > 0. This result has been proved by purely elementary methods. But in order
to know whether the right-hand side of (7.2) is convergent or not for values of s less than
or equal to zero we require the help of theorems which have only been established by
transcendental methods.
Now the right-hand side of (7.2) is an ordinary Dirichlets series for
1
s (n) .
(s + 1)
The first factor is a finite Dirichlets series and so an absolutely convergent Dirichlets series.
It follows that the right-hand side of (7.2) is convergent whenever the Dirichlets series for
1/(s + 1), viz.
X (n)
(7.3) ,
n1+s
is convergent. But it is known that the series (7.3) is convergent when s = 0 and that its
sum is 0.
It follows from this that
Nothing is known about the convergence of (7.3) when 12 < s < 0. But with the assump-
tion of the truth of the hitherto unproved Riemann hypothesis it has been proved that
(7.3) is convergent when s > 12 . With this assumption we see that (7.2) is true when
s > 21 . In other words, if 12 < s < 12 , then
c1 (n) c2 (n) c3 (n)
(7.5) s (n) = (1 s) + 1s + 1s +
11s 2 3
s c1 (n) c2 (n) c3 (n)
= n (1 + s) + 1+s + 1+s + .
11+s 2 3
Landau, Handbuch, p. 591.
Littlewood, Comptes Rendus, 29 Jan. 1912.
238 Paper 21
8. It is known that all the series obtained from (7.3) by term-by-term differentiation with
respect to s are convergent when s = 0, and it is obvious that the derivatives of s (n)
with respect to s are all finite Dirichlets series and so absolutely convergent. It follows
that all the derivatives of the right-hand side of (7.2) are convergent when s = 0; and so
we can equate the coefficients of like powers of s from the two sides of (7.2). Now
1
(8.1) = s s2 + ,
(s + 1)
where is Eulers constant. And
X X X
s (n) = s = 1s log + ,
where = n. Hence
Now equating the coefficients of s and s2 from the two sides of (7.2) and using (8.1) and
(8.2), we obtain
(8.4) c1 (n)(log 1)2 + 12 c2 (n)(log 2)2 + 13 c3 (n)(log 3)2 + = d(n)(2 + log n).
9. I shall now find an expression of the same kind for (n), the number of numbers prime
to and not exceeding n. Let p1 , p2 , p3 , . . . be the prime divisors of n, and let
(9.1) s (n) = ns (1 ps s s
1 )(1 p2 )(1 p3 ) ,
F (u.v) = (u)v s .
where t is any number not less than n. If s > 0 we can make t , as in 6. Then we
have
s (n) X () X (2)
(9.3) s
= c1 (n) s+1
+ c2 (n) + .
n (2)s+1
1 1
In particular
10. I shall now consider an application of the main formul to the problem of the number
of representations of a number as the sum of 2, 4, 6, 8, . . . squares. We require the following
preliminary results.
(1) Let
X 1s1 x 2s1 x2 3s1 x3
(10.1) D(n)xn = X1 = + + + .
1+x 1 x2 1 + x3
We shall choose
F (u, v) = v s1 , u 1( mod 2),
F (u, v) = v s1 , u 2( mod 4),
F (u, v) = (2s 1)v s1 , u 0( mod 4).
240 Paper 21
Then from (3.1) we can shew, by arguments similar to those used in 6, that
if s > 1.
(2) Let
X 1s1 x 2s1 x2 3s1 x3
(10.2) D(n)xn = X2 = + + + .
1x 1 + x2 1 x3
We shall choose
F (u, v) = v s1 , u 1( mod 2),
F (u, v) = v s1 , u 2( mod 4),
F (u, v) = (1 2s )v s1 , u 0( mod 4).
Then we obtain as before
D(n) = ns1 (1s + 3s + 5s + ){1s c1 (n) 2s c4 (n) + 3s c3 (n)
(10.21)
4s c8 (n) + 5s c5 (n) 6s c12 (n) + 7s c7 (n) 8s c16 (n) + }.
(3) Let
X 1s1 x 2s1 x2 3s1 x3
(10.3) D(n)xn = X3 = + + + .
1 + x2 1 + x4 1 + x6
We shall choose
F (u, v) = 0, u 0( mod 2),
F (u, v) = v s1 , u 1( mod 4),
F (u, v) = v s1 , u 3( mod 4).
Then we obtain as before
(4) We shall also require a similar formula for the function D(n) defined by
X 1s1 x 3s1 x3 5s1 x5
(10.4) D(n)xn = X4 = + .
1x 1 x3 1 x5
The formula required is not a direct consequence of the preceding analysis, but if, instead
of starting with the function
X 2n
cr (n) = cos ,
r
On certain trigonometrical sums and their applications in the theory of numbers 241
where is prime to r and does not exceed r, and proceed as in 23, we can shew that
It should be observed that there is a correspondence between cr (n) and the ordinary -
function of the one hand and sr (n) and the function
(s) = 1s 3s + 5s
then
r2s (n) = 2s (n) + e2s (n),
where e2s (n) = 0 when s = 1, 2, 3 or 4 and is of lower order than 2s (n) in all cases; that
if s is a multiple of 4 then
X s
(11.1) (1s + 3s + 5s + ) 2s (n)xn = X1 ;
(s 1)!
if s is of the form 4k + 2 then
X s
(11.2) (1s + 3s + 5s + ) 2s (n)xn = X2 ;
(s 1)!
if s is of the form 4k + 1 then
X s
(11.3) (1s 3s + 5s ) 2s (n)xn = (X3 + 21s X4 );
(s 1)!
See Landau, Handbuch, pp. 414 et seq.
Transactions of the Cambridge Philosophical Society Vol.XXII, 1916, pp. 159 184. [No.18 of this
volume; see in particular 24 28, pp. 202 208].
For a more precise result concerning the order of e2s (n) see 15.
242 Paper 21
x3 x5
P n x
2 (n)x = 4 +
1 x 1 x3 1 x5
(11.5)
x2 x3
x
= 4 + + +
1 + x2 1 + x4 1 + x6
s ns1 s
2s (n) = {1 c1 (n) + 2s c4 (n) + 3s c3 (n) + 4s c8 (n)
(11.11) (s 1)!
+5s c5 (n) + 6s c12 (n) + 7s c7 (n) + 8s c16 (n) + };
s ns1 s
2s (n) = {1 c1 (n) 2s c4 (n) + 3s c3 (n) 4s c8 (n)
(11.21) (s 1)!
+5s c5 (n) 6s c12 (n) + 7s c7 (n) 8s c16 (n) + };
s ns1 s
2s (n) = {1 c1 (n) + 2s s4 (n) 3s c3 (n) + 4s s8 (n)
(11.31) (s 1)!
+5s c5 (n) + 6s s12 (n) 7s c7 (n) + 8s s16 (n) + };
s ns1 s
2s (n) = {1 c1 (n) 2s s4 (n) 3s c3 (n) 4s s8 (n)
(11.41) (s 1)!
+5s c5 (n) 6s s12 (n) 7s c7 (n) 8s s16 (n) + };
From (11.5) and the remarks at the end of the previous section, it follows that
but this of course not such an elementary result as the preceding ones.
On certain trigonometrical sums and their applications in the theory of numbers 243
s ns1 s
2s (n) = {1 c1 (n) + 2s c4 (n) + 3s c3 (n) + 4s c8 (n)
(11.6) (s 1)!
+5s c5 (n) + 6s c12 (n) + 7s c7 (n) + 8s c16 (n) + },
12. We can obtain analogous results concerning the number of representations of a number
as the sum of 2, 4, 6, 8, . . . triangular numbers. Equation (147) of my former paper is
equivalent to
X
(12.1) (1 2x + 2x4 2x9 + )2s = 1 + 2s (n)(x)n
1
q
1 1 1 1
(12.3) ( 21 )x 24 f (x) = x 12 f (x 2 ), x 12 f (x2 ) = x 24 f (x ).
P
Finally 1 + 1 2s (n)(x)n can be expressed in powers of x by using the formula
then
X f 4s (x2 ) X f 24n (x)
e2s (n)xn = Kn (x)n ,
f 2s (x) f 24n (x2 )
1
1n 4 (s1)
(n)xn =
( 21 )s 1 s
(1s + 3s + 5s + )
P
2s x 4
(s 1)!
(12.61) s1
2s1 x2 3s1 x3
1 x
+ + +
1 x2 1 x4 1 x6
if s is a multiple of 4;
(n)xn =
2( 14 )s 1 s
(1s + 3s + 5s + )
P
2s x 4
(s 1)!
(12.62) 1 3 5
s1 s1 s1
1 x + 3 x + 5 x +
2 2 2
1x 1 x3 1 x5
if s is of the form 4k + 2;
X 2( 18 )s 1 s
(12.63) (1s 3s + 5s )
2s (n)xn = x 4
(s 1)!
1 3 5 1 3 5
!
1s1 x 4 3s1 x 4 5s x 4 1s1 x 4 3s1 x 4 5s1 x 4
1 + 3 + 5 + + 1 3 + 5
1 + x2 1 + x2 1 + x2 1 x2 1 x2 1 x2
if s is of the form 4k + 1 (except when s = 1); and
X 2( 18 )s 1 s
(12.64) (1s 3s + 5s )
2s (n)xn = x 4
(s 1)!
1 3 5 1 3 5
!
1s1 x 4 3s1 x 4 5s x 4 1s1 x 4 3s1 x 4 5s x 4
1 + 3 + 5 + 1 + 3 5 +
1 + x2 1 + x2 1 + x2 1 x2 1 x2 1 x2
On certain trigonometrical sums and their applications in the theory of numbers 245
It is easy to see that the principal results proved about e2s (n) in my former paper are also
true of e2s (n), and in particular that
e2s (n) = 0
when s = 1, 2, 3 or 4, and
r2s (n) 2s (n)
for all values of s.
(1s + 3s + 5s + )2s
(n)
is the coefficient of xn in
1 3
!
2( 14 )s 1 s 1s1 x 2 2s1 x 3s1 x 2
(13.1) x 4 + + + .
(s 1)! 1x 1 x2 1 x3
Similarly from (12.63) and (12.64) it follows that, if s is an odd integer greater than 1, then
(n) is the coefficient of xn in
(1s 3s + 5s )2s
1 1 3
!
4( 18 )s 1 s 1s1 x 4 2s1 x 2 3s1 x 4
(13.2) x 4 1 + + 3 + .
(s 1)! 1 + x2 1+x 1 + x2
Now by applying our main formul to (12.61) and (13.1) and (13.2) we obtain:
( 12 )s
(n)
2s = (n + 41 s)s1
(13.3) (s 1)!
{1s c1 (n + 14 s) + 3s c3 (n + 14 s) + 5s c5 (n + 14 s) + }
if s is a multiple of 4;
( 21 )s
(n) =
2s (n + 14 s)s1
(13.4) (s 1)!
{1s c1 (2n + 12 s) + 3s c3 (2n + 21 s) + 5s c5 (2n + 12 s) + }
246 Paper 21
( 21 )s
(1s + 3s + 5s + )2s
(n) = (n + 14 s)s1
(s 1)!
( ! !
sin(n + 41 s) sin(n + 41 s)
(14.6) 1s + 3s
sin(n + 41 s) sin 13 (n + 41 s)
! )
s sin(n + 14 s)
+5 +
sin 15 (n + 41 s)
if s is a multiple of 4;
( 12 )s
(1s + 3s + 5s + )2s
(n) = (n + 14 s)s1
(s 1)!
( ! !
s sin(2n + 12 s) sin(2n + 12 s)
(14.7) 1 + 3s
sin(2n + 12 s) sin 31 (2n + 12 s)
! )
s sin(2n + 21 s)
+5 +
sin 15 (2n + 21 s)
if s is twice an odd number;
(14.8)
( 12 )s
(1s 3s + 5s )2s
(n) = (n + 14 s)s1
(s 1)!
( !
sin(4n + s) sin(4n + s)
1s 3s
sin(4n + s) sin 13 (4n + s)
! )
s sin(4n + s)
+5
sin 15 (4n + s)
if s is an odd number greater than 1; and
!
sin(4n + 1) 1 sin(4n + 1)
r2 (n) = 2 (n) = 3
sin(4n + 1) sin 31 (4n + 1)
(14.9) ! )
sin(4n + 1)
+ 15 .
sin 51 (4n + 1)
248 Paper 21
In all these equations the series on the right hand are finite Dirichlets series and therefore
absolutely convergent.
But the series (14.3) is (as easily shewn by actual multiplication) the product of the two
series
1s c1 (n) + 2s c2 (n) +
and
ns1 (1s + 2s + 3s + ).
We thus obtain an alternative proof of the formul (7.5). Similarly taking the previous
expression of 2s (n). viz. the right-hand side of (11.6), and multiplying it by the series
1s + (3)s + 5s + (7)s +
we can shew that the product is actually the right-hand side of (14.4). The formul for
(n) can be disposed off similarly.
2s
15. The formul which I have found are closely connected with a method used for another
purpose by Mr. Hardy and myself . The function
X
(15.1) (1 + 2x + 2x4 + 2x9 + )2s = r2s (n)xn
has every point of the unit circle as a singular point. If x approaches a rational point
exp(2pi/q) on the circle, the function behaves roughly like
s (p,q )s
(15.2) ,
{(2pi/q) log x}s
1 X
(15.4) = p(n)xn ,
(1 x)(1 x2 )(1 x3 )
Asymptotic formul in Combinatory Analysis, Proc. London Math. Soc., Ser.2, Vol. XVII, 1918, pp.
75 115 [No.36 of this volume].
On certain trigonometrical sums and their applications in the theory of numbers 249
was to approximate to the coefficients by means of a sum of a large number of the coefficients
of these auxiliary functions. This method leads, in the present problem, to formul of the
type
1
r2s (n) = 2s (n) + O(n 2 s ),
the first term on the right-hand side presenting itself precisely in the form of the series
(11.11) etc.
It is a very interesting problem to determine in such cases whether the approximate formula
gives an exact representation of such an arithmetical function. The results proved here shew
that, in the case of r2s (n), this is in general not so. The formula represents not r2s (n) but
(except when s = 1) its dominant term 2s (n), which is equal to r2s (n) only when s = 1, 2, 3
or 4. When s = 1 the formula gives 22 (n) .
Suppose that
X sin{(2n + 1)/r}
1
Tr (n) = 2 1 ,
sin(/r)
(16.2)
X sin{(2n + 1)/r}
1
Ur (n) = 2 ,
sin(/r)
and
Ur (n) = Tr (n) + 21 (r),
where (n) is the same as in 9. Since cr (n) = O(1) as r , it follows that
Since
X (n) (s)
=
1
s+1 (s + 1)
if s > 1, (16.3) can be written as
(16.31)
s (1)s (2) + + s (n) = (s + 1)
U2 (n) U3 (n) U4 (n)
1
n + 2 + s+1 + s+1 + s+1 + 12 (s),
2 3 4
if s > 1. Similarly from (8.3), (8.4) and (11.51) we obtain
17. We shall now find a relation between the functions (16.1) and (16.3) which enables us
to determine the behaviour of the former for large values of n. It is easily shewn that this
function is equal to
n h n is X n h i X n
s n
X
s s s
(17.1) 1 + 2 + 3 + + + [ n] s.
=1
=1
=1
Now
(k + 12 )s+1
1s + 2s + + ks = (s) + + O(ks1 )
s+1
for all values of s, it being understood that
(k + 12 )s+1
(s) +
s+1
and hni
s= n s1 12 s + s .
It follows from these equations and (17.1) that
t
X 1 n s+1
s (1) + s (2) + + s (n) = (s) + + n s1
(17.2) s+1
=1
s (n + ) s + O ns1
o
n s
+ + s1 .
Acta Mathematica, Vol.XXXVII, 1914, pp. 113 140(p.140).
252 Paper 21
Suppose now that s > 0. Then, since varies from 1 to t, it is obvious that
s+1 ns1
< s1
n
and so
s+1 ns+1
O =O .
n s1
. Also
t
X
{ns (s) (s)} = ( n 1
2 + ){ns (s) (s)};
=1
t
X s n s+1 sns+1 ns+1 1
= (1 + s) ( n + )s + O(n 2 s );
1+s 1+s s+1
=1
t
s ns n 1
( n + )s + O(n 2 s );
X
n s1 = (1 s) +
=1
1s 1s 1s
t
( n + )2+s 1
+ O(n 2 s );
X
s
( n + ) = ( n + )(s) +
=1
1+s
t
n s ns 1
( n + )2s + O(n 2 s );
X
( n + ) = ns ( n + )(s) +
1s
=1
and
t
ns1
X
O = O(m),
s1
=1
On certain trigonometrical sums and their applications in the theory of numbers 253
where
1
(17.4) m = n 2 s (s < 2), m = n log n(s = 2), m = ns1 (s > 2).
n1+s
(17.7) s (1) + s (2) + + s (n) = (1 + s) + 21 ns (s)
1+s
sn s T2 (n) T3 (n) T4 (n)
+ (1 s) + n (1 + s) + s+1 + s+1 + + O(m),
s1 2s+1 3 4
for all positive values of s. If s > 1, the right-hand side can be written as
ns
(1 s) + ns (1 + s)
s1
(17.8)
n 1 U2 (n) U3 (n) U4 (n)
+ + s+1 + s+1 + s+1 + + O(m).
1+s 2 2 3 4
This result has been proved by Landau. See his report on Wigerts memoir in the Gottingische gelehrte
Anzeigen, 1915, pp. 377 414 (p.402). Landau has also, by a more transcendental method, replaced O( n)
2
by O(n 5 ) (loc.cit., p.414).
254 Paper 21
2 2 1
1 (1) + 1 (2) + + 1 (n) = n + 2 n( 1 + log 2n)
12
(17.9)
2 n T2 (n) T3 (n) T4 (n)
+ + + + + O( n).
6 22 32 42
or
(s)(r + s 1) X X cm (n)
= r ns
,
(r) 1 1
m
from which we deduce
X cm (1) cm (2) cm (3)
(s) ()1s = + + + ,
1s 2s 3s
being a divisor of m and its conjugate. The series on the right-hand side is convergent
for s > 0 (except when m = 1, when it reduces to the ordinary series for (s)).
When s = 1, m > 1 we have to replace the left-hand side by its limit as s 1. We find
that
(m) being the well-known arithmetical function which is equal to log p if m is a power of
a prime p and to zero otherwise.